Fenomena kehadiran BANK ASI terhadap Konsep Kemarhaman karena Radha’ah - Mawardi, Mawardi; Nurcahaya, Nurcahaya (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
ASI BANK is a new breakthrough that has emerged in contemporary fiqh discussions, where breast milk (ASI) can be donated or sold, and provided in one place. This certainly needs to be studied in depth, considering that if a baby under the age of 2 years breastfeeds a woman who is not his biological mother then a mahram relationship occurs because of the mutual milk between them. This is what the author will discuss in this article, so that readers can find out about the issue of BANK ASI and can find out what the law is about consuming breast milk through BANK ASI. This research uses qualitative methods with the type of library research by collecting data from various library sources in the form of journal articles and research that has been carried out by other people. In this article, it is concluded that the author is more inclined towards the opinion that prohibits the establishment and consumption of breast milk from ASI BANK based on several reasons, including because it maintains the goal of the Shari'ah, namely "hifzul Nasl (protecting offspring). Keywords: Breast Milk Bank, Mahram, Radha'ah.